Pigmented epidermal cyst with dense collection of melanin: A rare entity - Report of a case with review of the literature - P S Jayalakshmy; K Subitha; P V Priya; Gerald Johnson (Wolters Kluwer Medknow Publications, 2012)
Epidermal cyst is a very common benign cystic lesion of the skin. It is usual to find ulceration of the lining epithelium, rupture of the cyst wall with chronic inflammation and foreign body giant cell reaction. But, it is very rare to see an epidermal cyst with marked accumulation of melanin pigment. Only a few cases of pigmented epidermal cyst with dense collection of melanin pigment have been published in the literature. Here, we are reporting a case of ruptured epidermal cyst with keratin granuloma formation and showing dense collection of melanin pigment.